Psychological mechanisms of deviant personality - Valickas, Gintautas (Psichologija, 1995)
The article deals with different aspects of development of deviant personality: 1. General mechanisms of the development of personality and its functioning in particular conditions. 2. The reciprocity between internal and external factors of development of personality. 3. Value system and self-esteem of personality and its role in development of deviant behaviour. The analysis of various data suggests that the striving to raise one's self-esteem is a general nonspecific factor, which may stimulate various forms of deviant behaviour. The main point in the development of positive self-esteem is the reorientation of personality to another (deviant) value system. Different means of neutralization of internal and external demand are analysed as the intermediate in the process of the reorientation of personality from prosocial to antisocial way of development.
Keywords: personality; deviant personality; development of personality